2010
DOI: 10.3109/0886022x.2010.504910
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia, fatigue, and plasma interleukin-6 levels in chronic hemodialysis patients

Abstract: This study aimed at evaluating the possible relationship between anorexia and fatigue in hemodialysis (HD) patients and at measuring the plasma levels of interleukin-6 (IL-6) and C-reactive protein (CRP) in HD patients with or without anorexia and/or fatigue. The first question of the Hemodialysis Study Appetite questionnaire was used to assess the appetite of the HD patients and the vitality scale of the SF-36 to assess fatigue. The Charlson Comorbidity Index was assessed in each patient. Seventy-six HD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
6
31
0
2
Order By: Relevance
“…In this situation, patients could experience stress and emotion fluctuation, all of which resulted in tiredness, exhaustion, and an increase in patients' fatigue level. 50 In our present study, less than one-third of MHD patients exercised more than one hour per day. A physical exercise program was found to be one of the positive factors in managing fatigue.…”
mentioning
confidence: 89%
“…In this situation, patients could experience stress and emotion fluctuation, all of which resulted in tiredness, exhaustion, and an increase in patients' fatigue level. 50 In our present study, less than one-third of MHD patients exercised more than one hour per day. A physical exercise program was found to be one of the positive factors in managing fatigue.…”
mentioning
confidence: 89%
“…The principal obstacles to improving our understanding and treatment of fatigue in ESRD patients are the relative paucity of data on its correlates and clinical implications, conflicting findings and a dearth of longitudinal data on the potentially modifiable correlates. Multiple physiologic, psychological, sociodemographic and treatment-related factors are likely associated with fatigue, but their complex and reciprocal interactions with fatigue are poorly understood [1,2,11,12]. If fatigue influences health- related quality of life (HRQOL) and/or survival, there would be a strong rationale for identification of fatigue and its correlates early in HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that appetite is independently associated with many other symptoms such as symptoms of depression [11], fatigue [10] and gastrointestinal symptoms [9]. Consistently, a longer time of recovery also has been shown to be associated with fatigue [13], gastrointestinal symptoms such as nausea and vomiting [12], and symptoms of depression [12].…”
Section: Discussionmentioning
confidence: 71%
“…It has been proposed that uremic toxins such as middle molecules, inflammation, altered pattern of amino acids, hormones and peptides may be involved [4,5,6,7,8]. Recently, we have shown that poor appetite is independently associated with gastrointestinal symptoms [9], fatigue [10] and symptoms of depression [11]. Similarly to anorexia in cancer, it seems that anorexia in HD patients is not an isolated symptom, but part of a complex of symptoms.…”
Section: Introductionmentioning
confidence: 99%